Redox regulation by SOD2 modulates colorectal cancer tumorigenesis through AMPK‐mediated energy metabolism - Zhou, Chen; Lyu, Li‐hua; Miao, Hui‐kai; Bahr, Tyler; Zhang, Qiong‐ying; Liang, Ting; Zhou, Huai‐bin; Chen, Guo‐rong; Bai, Yidong (Molecular carcinogenesis, 2020)
Colorectal cancer (CRC) is a common malignancy. Many reports have implicated aberrant mitochondrial activity in the progression of CRC, with particular emphasis on the dysregulation of redox signaling and oxidative stress. In this study, we focused on manganese superoxide dismutase (MnSOD/SOD2), a key antioxidant enzyme, which maintains intracellular redox homeostasis. Current literature presents conflicting mechanisms for how SOD2 influences tumorigenesis and tumor progression. Here, we explored the role of SOD2 in CRC specifically. We found high levels of SOD2 expression in CRC tissues. We carried out a series of experiments to determine whether knockdown of SOD2 expression in CRC cell lines would reverse features of tumorigenesis. We found that reduced SOD2 expression decreased cell proliferation, migration, and invasion activity in CRC cells. Results from an additional series of experiments on mitochondrial function implicated a dual role for SOD2 in promoting CRC progression. First, proper level of SOD2 helped CRC cells maintain mitochondrial function by disposal of superoxide (O2.−). Second, over‐expression of SOD2 induced H2O2‐mediated tumorigenesis by upregulating AMPK and glycolysis. Our results indicate that SOD2 may promote the occurrence and development of CRC by regulating the energy metabolism mediated by AMPK signaling pathways.